Masson, J. L. y Kosambi, D. D. (Trad.), Avimāraka (Love's Enchanted World) UNESCO Collection of Representative Works — Indian Series, Motilal Banarsidas, Delhi, Patna, Varanasi, 1970. - G. S., S. (El Colegio de México, 1973)
-